2003
DOI: 10.1007/s00415-003-1053-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoimmune thyroiditis and non-immune thyroid disease in multiple sclerosis

Abstract: Since multiple sclerosis (MS) and autoimmune thyroiditis (AIT) are presumed to be of autoimmune origin the correlation of these two diseases is of special interest. The aim of this study was to determine whether there are differences in the prevalence of thyroid disease with special emphasis on AIT compared with MS and normal subjects and whether the presence of thyroid disease correlates with disability, disease course, age, and disease duration. 353 consecutive patients with clinically definite MS, without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 27 publications
1
34
1
4
Order By: Relevance
“…Hypothyroidism caused by Hashimoto thyroiditis displays a tendency to be more severe and more common in MS patients (5).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothyroidism caused by Hashimoto thyroiditis displays a tendency to be more severe and more common in MS patients (5).…”
Section: Resultsmentioning
confidence: 99%
“…38 antiTPO sentezinden sorumlu olabileceği öne sü-rülmektedir. MS hastalarında tiroid antikoru yük-sekliği görülme oranı ise %4-22 arasında değiş-mektedir.…”
Section: Discussionunclassified
“…In particular it was demonstrated that males with MS have the same prevalence of thyroid disorders as women, with or without MS [8]. At baseline alterations of thyroid hormones and/or thyroid stimulating hormon (TSH) were observed in 5.3% of patients [7].…”
Section: Introductionmentioning
confidence: 99%